Job Insecurity and Financial Distress - Caterina Giannetti; Marianna Madia; Luigi Moretti (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2013)
This paper investigates the effects of different job categories on households' likelihood of experiencing financial distress. Given imperfect financial markets and the absence of unemployment subsidies, households with less secure jobs are likely to experience drops in income more frequently than households with well-protected jobs. Households' abilities to deal with financial decisions (i.e. financial literacy) can mitigate these problems. Our results suggest that greater job insecurity increases the probability of being in financial distress similarly than other working statuses (e.g. unemployment), and in some cases even more (i.e. part-time workers). However, a high level of financial literacy can counterbalance this effect, especially for atypical workers.
Keywords: C23; C25; D14; 330